Case report: Hydrometrocolpos conditioning recurrent urinary tract infections - Malanowska, Ewelina; Krzyścin, Mariola; Sowińska-Przepiera, Elzbieta; Starczewski, Andrzej; Sulikowski, Tadeusz; Balzarro, Matteo; Rubilotta, Emanuele (Frontiers in Surgery, 2022)
We present a case of 12 1/12-old-girl, who suffered from recurrent urinary tract infections for many years but never undergone a detailed diagnostic process. Only as a teenager, when she complained with acute pain in lower abdomen, it turned out that her genital organs were not properly developed. She had namely an obstructive defect in reproductive tract. When the significant amount of discharge collected in the lumen of genital tract and the organs had distended an acute pain appeared which allowed us to set the diagnosis. In the diagnostic process a transperineal ultrasonography showed to be extremely helpful and allowed us to establish the type and thickness of the obstacle. The patient underwent the excision of transverse vaginal septum and postoperative silicon dilators were used to prevent the recurrence of the obstruction. No recurrence of urinary infection or complications occurred throughout 11 months of follow-up.